Cassava leaves and stems hydrolysis for glucose production - Azmi, Azlin Suhaida; Shaharuddin, Khairulbariah; Mel, Maizirwan (IIUM Press, International Islamic University Malaysia, 2017)
Cassava or tapioca leaves and stems are all year product that is far under researched and underutilized. It was reported that the leave contain essential minerals and nitrogen sources required by microorganisms such as yeast and other fermenting microbes for growth. In this study, cassava leave and stem were hydrolyzed using diluted acid concentration for glucose production. The research was conducted in shake flask and Taguchi’s methodology was used to study significant parameters affecting hydrolysis process. Design expert v8.0 software aided the analysis for maximum glucose production. Validation result revealed that hydrolysis of 5% (w/v) mixture of cassava stems and leaves gave maximum of glucose yield of 0.991 g/g.